From Data to Action: Transforming Bradford's Perinatal Mental Health Intelligence Through Local Collaboration - Henderson, Hollie; Shaib, Sabah; Milne, Lisa; Ciesla, Kayley; Bridges, Sally (International Journal of Population Data Science, 2025)
Objective The objective was to work with local services in Bradford to improve the quality of routine perinatal mental health data for research and service planning. This stemmed from analysis of locally linked routine data, which identified significant gaps and issues, and the motivation of services to better use their data. Methods Born in Bradford for All (BiB4All) is an electronic data linkage cohort of mothers and their children, which aims to use routinely collected data for research and to inform local policy and practice. To achieve this aim, we established links with relevant stakeholder groups in Bradford, to understand their current priorities. Through attending stakeholder meetings, we identified a common goal of improving routine perinatal mental health data across services in Bradford, to enable a better understanding of inequalities and unmet need. We co-produced a research question and analysis of BiB4All data to explore the extent of the current data issues. Results Establishing a trusted relationship between local services recording routine data and researchers using these data enabled the co-design of a workshop aiming to develop an action plan to address identified data issues. The workshop (planned for April 2025) is underpinned by Ketso principles and will bring together local maternity, health visiting and specialist perinatal mental health services in Bradford to discuss: Their current data assets, based on insights from the BiB4All data analysis How to improve their data Barriers to improving their data Next steps for implementing changes to data collection This collaboration has developed understanding among perinatal mental health services about how routine data can be used beyond individual clinical care for research and service planning. Conclusion Building capacity for routine data to be used for research and service improvements is an important step to more equitable access and uptake to perinatal mental health services. We are planning an evaluation to understand the impact of this work on data quality, service access and inclusion.